THE EFFECT OF REBRANDING AND BRAND SIGNATURE ON MAKO BRAND PERFORMANCE IN TANGERANG, MEDIATED BY BRAND REPUTATION - Lin, Felishia Janice; Widjaja, William (International Humanities and Applied Science Journal, 2025)
This study aims to identify and analyze the influence of rebranding, brand signature, and brand reputation on the performance of the Mako Cake and Bakery brand. This study uses a quantitative approach with a purposive sampling technique through a Google Forms questionnaire survey. The sample in this study was 357 Mako Cake and Bakery customers in the Tangerang area. The analysis technique used was Partial Least Square analysis using SmartPLS 3 software. The results of this study indicate that the Rebranding (X1) and Brand Reputation (M) variables have a significant positive effect on Brand Performance (Y). Conversely, Brand Signature (X2) does not have a significant effect on Brand Performance (Y). There is a significant positive indirect effect on Rebranding (X1) on Brand Performance (Y) through the mediation of Brand Reputation (M).